# Difference between revisions of "Integration by parts for delta integrals with no sigma in integrand"

From timescalewiki

Line 5: | Line 5: | ||

==Proof== | ==Proof== | ||

+ | |||

+ | ==See also== | ||

+ | [[Integration by parts for delta integrals with sigma in integrand]]<br /> | ||

==References== | ==References== |

## Revision as of 14:47, 13 March 2018

## Contents

## Theorem

The following formula holds: $$\int_a^b f(t) g^{\Delta}(t) \Delta t = (fg)(b) - (fg)(a) - \int_a^b f^{\Delta}(t) g(\sigma(t)) \Delta t,$$ where $\int$ denotes the delta integral.

## Proof

## See also

Integration by parts for delta integrals with sigma in integrand